Thermoregulatory effects of swaddling in Mongolia: a randomised controlled study. Issue 2 (29th October 2015) - Tsogt, Bazarragchaa; Manaseki-Holland, Semira; Pollock, Jon; Blair, Peter S; Fleming, Peter
Abstract : Objective: To investigate thermal balance of infants in a Mongolian winter, and compare the effects of traditional swaddling with an infant sleeping-bag in apartments or traditional tents (Gers). Design: A substudy within a randomised controlled trial. Setting: Community in Ulaanbaatar, Mongolia. Subjects: A stratified randomly selected sample of 40 swaddled and 40 non-swaddled infants recruited within 48 h of birth. Intervention: Sleeping-bags and baby outfits of total thermal resistance equivalent to that of swaddled babies. Outcome measure: Digital recordings of infants' core, peripheral, environmental and microenvironmental temperatures at 30-s intervals over 24 h at ages 1 month and 3 months. Results: In Gers, indoor temperatures varied greatly (<0–>25°C), but remained between 20°C and 22°C, in apartments. Despite this, heavy wrapping, bed sharing and partial head covering, infant core and peripheral temperatures were similar and no infants showed evidence of significant heat or cold stress whether they were swaddled or in sleeping-bags. At 3 months, infants in sleeping-bags showed the 'mature' diurnal pattern of a fall in core temperature after sleep onset, accompanied by a rise in peripheral temperature, with a reverse pattern later in the night, just before awakening. This pattern was not related to room temperature, and was absent in the swaddled infants, suggesting that the mature diurnal pattern may develop later in them. Conclusions: No evidence of cold stress was found. Swaddling had no identifiable thermal advantages over sleeping-bags during the coldest times, and in centrally heated apartments could contribute to the risk of overheating during the daytime. Trial registration number: ISRTN01992617.